The Impact of belajar.id Account Integrated with Quizizz on Learning Quality - Lestari, Novia Ayu; Hamzah, Syukri; Wardana, Rendy Wikrama; April Yanti, Fitri (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2025)
This study aims to analyze the impact of the use of quizizz integrated belajar.id accounts on the quality of learning through literature studies. The results of the study are expected to provide knowledge that belajar.id account integrated with quizizz has a good impact and it is hoped that more educators will take advantage of it. This research method uses literature review by examining various journals, articles, books and other sources that are relevant to the topic of using belajar.id accounts that are integrated with the digital platform, namely quizizz on the quality of learning. Based on the results of this review literature reflected on the learning quality indicators based on several aspects, the use of quizizz integrated using belajar.id accounts have a positive impact. Therefore, educators can take advantage of this as a way to improve the quality of learning.